Cell growth and proliferation on the interface of a silk fabric tubular scaffold. Issue 20 (December 2016) - Sun, Xiaolong; Hao, Yunxia; Wang, Qiongyu; Dong, Fenglin; Wang, Jiannan
A silk fibroin tubular scaffold (SFTS) has been designed and fabricated using silk fabric and regenerated silk fibroin, and used in the construction of artificial blood vessels. As a replacement for blood vessels, scaffolds should have a suitable interface for the adherence and proliferation of vascular cells, and the pore structure of the internal surface is one of most important factors. In this article, we investigate the effect of SFTSs with different pore structures on cells growth. Pore structures were controlled by adjusting the concentration of both the silk fibroin and the polyethylene glycol diglycidyl ether cross-linker as well as the freezing temperature. Intuitive cell fluorescence imaging and MTT assays on fibroblasts and human umbilical vein endothelial cells (HUVEC) were used to probe interactions with internal surfaces of differing pore diameter and density. The results showed that SFTSs fabricated under different conditions exhibited no cytotoxicity. Furthermore, fibroblasts were highly migratory, occupied the interface and could bridge the macropores well when the pore diameter was 50 ∼ 75 µm. SFTSs with micropores of about 30 ∼ 50 µm in diameter were deemed suitable for the growth and proliferation of HUVECs.